Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can anything be said about the solutions of the following functional equation? $$ f(x, y + z) = f(x, y) + f(x + y, z) $$

I don't seem to be able to find much in what I think are the standard references in these cases.

Thanks for any tip.

share|cite|improve this question
Where did this functional equation come up? Here's a hint: try determining $f(n, m)$ for all pairs of integers $(n, m)$ by plugging in various integers until you see a pattern. If you do this then you might be able to figure out a formula when x and y are rational or real. – Jonah Sinick Oct 31 '12 at 18:58
up vote 5 down vote accepted

Following the beautiful idea of Robert Israel, we will show that the solutions of the equation are precisely functions of the form $f(x,y)=g(x+y)-g(x)$, where $g$ is an arbitrary function.

First, we plug $z = -y$ into the equation. This yields $$f(x, 0) = f(x, y) + f(x + y, -y).\tag{1}$$

In the case $y=0$, this tells us that $f(x,0)=0$ for all $x$, as Robert Israel already noticed. Using this fact in $(1)$, we have that $$f(x,y)=-f(x+y,-y)\tag{2}$$ must hold for all $x,y$ in order for $f$ to be a solution. We will now use this fact in the original equation. The original equation says that $$f(x, y) = f(x, y + z) - f(x + y, z)$$ holds for all $x,y,z$. Using $(2)$ twice we may rewrite this as $$f(x, y) = - f(x+y+z, - y - z) + f(x+y+z, -z)$$ Now, plug in $z=-x-y$ and get $$f(x, y) = - f(0, x) + f(0, x+y).$$ This means that if $f$ solves the original equation, we may define the function $g$ by $g(w)=f(0,w)$ and then $f(x,y)=g(x+y)-g(x)$ will hold. This shows that indeed the solutions of the equation are precisely of the form suggested by Robert Israel.

share|cite|improve this answer
Thanks a lot! :) – kenshin Nov 3 '12 at 11:52

Take $y=0$ to get $f(x,z) = f(x,0) + f(x,z)$, so $f(x,0) = 0$.

$f(x,y) = g(x+y) - g(x)$ is a solution for arbitrary functions $g$. I don't know if those are all the solutions: they seem to be all the ones that are low-degree polynomials.

EDIT: Note that the transformation $f(x,y) = F(x,x+y)$ and change of variables $x = X, y = Y-X, z = Z - Y$ makes the equation $$ F(X,Z) = F(X,Y)+F(Y,Z)$$ Thus (taking, say, $Y=0$, $G(X) = F(X,0)$ and $H(Z) = F(0,Z)$) we have $F(X,Z) = G(X) + H(Z)$. But then $G(X) + H(Z) = G(X) + H(Y) + G(Y) + H(Z)$ which says $G(Y) = -H(Y)$. So we have $F(X,Z) = H(Z) - H(X)$, which transforms back to $f(x,y) = H(x+y) - H(x)$.

share|cite|improve this answer
I borrowed your idea in my answer below. I hope you don't mind. – Dejan Govc Oct 31 '12 at 19:46
thank you very much! – kenshin Nov 3 '12 at 11:51

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.